Artificially dried corn in cattle rations - Richardson, D.; Smith, E.F.; Koch, B.A.; Ward, J.K.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
With improved harvesting machinery, farmers tend to harvest grain earlier to prevent loss by lodging or inclement weather. This often results in grain being too high in moisture for normal storage, and means that it must be stored in an air-tight container or dried, if it is to enter normal storage. There are ways of drying grain with and without heated air.The corn was produced at the Courtland Irrigation Research Farm near Belleville. The drying was done by the University’s agricultural engineering department. All the corn came from the same field. Three lots of 10 heifer calves each were used. Sorghum silage was fed as the roughage and each animal received 1 pound of soybean oil meal daily. Minerals and salt were fed free choice.
Keywords: Beef; Corn; Drying grain